IMPROVING ELEMENTARY STUDENTS' HYGIENE BEHAVIOR THROUGH CTPS EDUCATION AND FACILITIES PROVISION IN COASTAL AND URBAN SCHOOLS OF KENDARI, INDONESIA - Sabilu, Yusuf; Handayani, Listy; Salsabila, Syefira; Nurfadilah H., Siti; Rohadi, Melia Pradita; Arifin, Muhammad; Yasmin, Dhira Fijri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Soil-transmitted helminth (STH) infections remain a significant health challenge in Indonesia, particularly among school-age children. This community service program aimed to increase students' knowledge and hygiene behavior through Clean and Healthy Living Behavior (PHBS) education, specifically handwashing with soap (CTPS), in two elementary schools: SDN 85 and SDN 94 Kendari. The intervention included interactive education sessions, CTPS demonstrations, educational materials distribution, and provision of portable handwashing stations. Pre-test and post-test assessments showed improved student knowledge and observed hygiene practices. The program's unique approach involved not only student-targeted education but also active coordination with school staff and facility enhancement. The results showed increased handwashing behavior, better awareness of hygiene, and positive feedback from both students and school personnel. Keywords: CTPS, elementary school, hygiene education, handwashing, sanitation, STH prevention